On the comparison of intersystem interference scenarios between IMT- Advanced and fixed services over various deployment areas at 3500 MHz - Shamsan, Z. A.; Rahman, T. A. (Faculty of Engineering, The University of Hong Kong, 2008)

(untitled)
At WRC-07, the frequency band 3500MHz has been allotted for the next generation of mobile International Mobile Telecommunication-Advanced (IMT-Advanced). Meanwhile this band is already in used by fixed services, which means that harmful interference probability may be transpired. In this paper, the coexistence between the two services in various geographical deployment areas (dense urban, urban, suburban, and rural areas) will be analyzed. Spectrum emission mask is an effective interference model will be invested and interference to noise ratio of âˆ’6dB is used as a coexistence criterion. Co-channel, zero-guard band, and adjacent channel are three intersystem interference scenarios will be investigated. The analysis will focus to determine required minimum separation distance and frequency separation under different attenuation due to local clutter and height of antennas at fixed channel bandwidth.